Metabolically activated and highly polyfunctional intratumoral VISTA+ regulatory B cells are associated with tumor recurrence in early-stage NSCLC - Domenico Lo Tartaro; Beatrice Aramini; Valentina Masciale; Nikolaos Paschalidis; Francesco Demetrio Lofaro; Anita Neroni; Rebecca Borella; Elena Santacroce; Alin Liviu Ciobanu; Anna Valeria Samarelli; Federica Boraldi; Daniela Quaglino; et al. (Molecular Cancer)
Abstract B cells have emerged as central players in the tumor microenvironment (TME) of non-small cell lung cancer (NSCLC). However, although there is clear evidence for their involvement in cancer immunity, scanty data exist on the characterization of B cell phenotypes, bioenergetic profiles and possible interactions with T cells in the context of NSCLC. In this study, using polychromatic flow cytometry, mass cytometry, and spatial transcriptomics we explored the intricate landscape of B cell phenotypes, bioenergetics, and their interaction with T cells in NSCLC. Our analysis revealed that TME contains diverse B cell clusters, including VISTA+ Bregs, with distinct metabolic and functional profiles. Target liquid chromatography-tandem mass spectrometry confirmed the expression of VISTA on B cells. VISTA+ Bregs displayed high metabolic demand and were able to produce different cytokines, including interleukin (IL)-10, transforming growth factor (TGF)-β, IL-6, tumor necrosis factor (TNF), and granulocyte–macrophage colony-stimulating factor (GM-CSF). Spatial analysis showed colocalization of B cells with CD4+/CD8+ T lymphocytes in TME. The computational analysis of intercellular communications that links ligands to target genes, performed by NicheNet, predicted B-T interactions via VISTA-PSGL-1 axis. Colocalization analyses revealed that PSGL-1 T cells and VISTA+ B cells are adjacent in the TME. Notably, tumor infiltrating CD8+ T cells expressing PSGL-1 exhibited enhanced metabolism and cytotoxicity. In NSCLC patients, prediction analysis performed by PENCIL revealed the presence of an association between PSGL-1+CD8+ T cells and VISTA+ Bregs with lung recurrence. Our findings suggest a potential interaction between Bregs and T cells through the VISTA-PSGL-1 axis, that could influence NSCLC recurrence.